Mitigating Stress through Empowerment A study with respect to Manufacturing sector organizations in Cochin, Kerala, India - Soumya Subramanian AND Ramkumar N (Asian Journal of Research in Social Sciences and Humanities, 2016)
A healthy workforce is the key to a healthy organization, and vice versa. Health refers to the physical as well as psychological well being. While it is important for an organization to provide adequate compensation, it is equally important to take care of their psychological well being as well. Psychological well being is ensured in a work environment which is stress free. According to a study conducted by Seibert, et al. (2011), “empowered employees were more satisfied and committed at work, and less likely to experience stress and to think about leaving the organization”. Stress can also lead to physical, psychological and behavioural problems that can affect the personal or family life of the employees. Thus, empowering the employees help to reduce stress thereby improving productivity, reducing turnover, contributing to the profit of the organization; thereby minimizing the individual problems caused due to stress. The current study examines the relation between empowerment and stress in the manufacturing sector organizations in Cochin region, Kerala, India. Simple random sampling was used to select 324 respondents from the population of skilled workers in the manufacturing organizations in the above said area. The study showed that empowerment is negatively related to stress.